How Uremic Toxins Alter Atorvastatin Disposition: Molecular Mechanisms of Inhibition of the Enzyme CYP3A4 - Ashna Asim; Fen Wang; Dong Pu; Sisi Wang; Dian Wang; Wenwen Li; Feng Yu; Li Ji (Balkan Medical Journal)
Background: In uremic patients, the accumulation of gut-derived protein-bound uremic toxins (PBUTs) induces changes in the microenvironment of the patients, leading to changes in the elimination pattern of drugs. Aims: To assess ways in which PBUTs alter the CYP450 enzymes in hepatocytes as well as the possible effects of specific PBUTs on the metabolism and excretion of atorvastatin (ATV). Study Design: An experimental study. Methods: The experimental group was treated with long-term MHD for > 3 months, estimated-glomerular filtration rate (e-GFR) < 15 ml/min, normal Alb level (35.0-55.0 g/l), and no urine; the control group was not treated with hemodialysis, e-GFR < 60 ml/min, normal Alb level, and normal urinary excretion function. A suitable UPLC-MS/MS method was developed for detecting the concentration of 4-hydroxy ATV. Fresh primary hepatocytes were isolated from rats, and the uptake of ATV was tested in the uremic serum (US) group, IS group, and HA group and compared with that in the normal serum group. The metabolic status of ATV in the US group, IS group, and HA group was compared with that in the ATV group. RLM were extracted, and the metabolic experiment of ATV was performed in a human CYP3A4 model. The influence of UTs on pregnane X receptor (PXR)/nuclear factor kappa B (NF-κB) mRNA and the protein expression was also detected. Results: IS and HA inhibited the ATV metabolism to varying degrees, wherein IS was the most potent inhibitor, producing > 50% inhibition. Meanwhile, the protein expression of CYP3A4 was downregulated after incubation with US, IS, and HA (p < 0.01). The excretion of ATV was also inhibited by 59.24% and 71.95% after incubation with IS and HA, respectively. The effects of uremic toxins on PXR/NF-κB mRNA and protein expression elucidated that PBUTs can inhibit ATV uptake and metabolism by exerting inhibitory effects on CYP3A4 through the PXR/NF-κB signaling pathway. Conclusion: ATV metabolism could be significantly altered in the presence of uremic toxins, suggesting a downregulated effect on the ATV uptake, possibly through Oatp1b1, and also on the activity of CYP3A4 through the PXR/NF-κB signaling pathway.